Membangun Identitas Jakarta Melalui Kampanye Plus Jakarta: Kota Kolaborasi - Matahariputri, Galuh Mawarni; Mansoor, Alvanov Zpalanzani; Nawawi, Dody Achmad (Serat Rupa: Journal of Design, 2024)
With the increasing intensity of urban competition, city branding strategies are becoming more widely adopted by major cities around the world, including Jakarta. Despite experiencing political turbulence, the Plus Jakarta City of Collaboration campaign is considered a breakthrough amongst other Indonesian city brands. The aim of this study is to question the success of the campaign to Anholt’s city branding hexagon theory using explanatory research and qualitative approach. This theory discusses six variables that create a successful city branding: presence, place, potential, pulse, people, and prerequisite. The study concludes that Plus Jakarta have succeeded in variables people and prerequisite and have shown efforts towards the other variables but have yet to succeed in them due to its short lifespan and having no support from the current government as stakeholder.